Prevalence of thyroid dysfunction in neonatal population - Kaur, Gunjanpreet; Arora, Sunita; Singh, Kamalpreet; Singh, Mandeep; Kaur, Arshpreet (International Journal of Contemporary Pediatrics, 2020)
Background: The objectives of this study was to study the prevalence of thyroid disorders in high risk neonatal populations and to study association of maternal thyroid dysfunction with neonatal thyroid problems and outcome. Methods: This was an observational study, conducted in NICU at Sri Guru Ram Das Institute of Medical Sciences and Research, Amritsar. The study included neonates born to mothers with thyroid disorder or with clinical features suggestive of thyroid dysfunction. Neonates with history of maternal thyroid dysfunction were screened at 72 to 96 hrs of postnatal age. Those with TSH >10 mIU/L or free T4 <1.1 ng /ml were followed up after two weeks. The neonates with clinical features suggestive of thyroid dysfunction were screened at presentation and those with abnormal thyroid profile were followed up after two weeks. Results obtained were statistically analyzed using SPSS 17.0 software. Results: Out of 260 neonates screened, 208 neonates were born to mothers with hypothyroidism, 6 neonates had increased levels of TSH during first week which normalised on follow up during third week. One neonate born to hyperthyroid mother, showed increased TSH levels during first week and 2nd week which declined to normal level on follow up at 3rd week. Out of 51 neonates with clinical features suggestive of thyroid dysfunction, born to euthyroid mothers, 3 neonates had increased levels of TSH on presentation which normalised on further follow up. Thus, majority of high risk neonates at birth show transient hypothyroidism. Conclusions: None of the neonate was labelled as hypothyroid, all the 10 neonates showed transient hyperthyrotropinemia.